Ironing Out the Unconventional Mechanisms of Iron Acquisition and Gene Regulation in Chlamydia - Pokorzynski, Nick D.; Thompson, Christopher C.; Carabeo, Rey A. (Frontiers in Cellular and Infection Microbiology, 2017)
The obligate intracellular pathogen Chlamydia trachomatis, along with its close species relatives, is known to be strictly dependent upon the availability of iron. Deprivation of iron in vitro induces an aberrant morphological phenotype termed “persistence.” This persistent phenotype develops in response to various immunological and nutritional insults and may contribute to the development of sub-acute Chlamydia¬-associated chronic diseases in susceptible populations. Given the importance of iron to Chlamydia, relatively little is understood about its acquisition and its role in gene regulation in comparison to other iron-dependent bacteria. Analysis of the genome sequences of a variety of chlamydial species hinted at the involvement of unconventional mechanisms, being that Chlamydia lack many conventional systems of iron homeostasis that are highly conserved in other bacteria. Herein we detail past and current research regarding chlamydial iron biology in an attempt to provide context to the rapid progress of the field in recent years. We aim to highlight recent discoveries and innovations that illuminate the strategies involved in chlamydial iron homeostasis, including the vesicular mode of acquiring iron from the intracellular environment, and the identification of a putative iron-dependent transcriptional regulator that is synthesized as a fusion with a ABC-type transporter subunit. These recent findings, along with the noted absence of iron-related homologues, indicate that Chlamydia have evolved atypical approaches to the problem of iron homeostasis, reinvigorating research into the iron biology of this pathogen.